Investigating the Relationship between Educational Dimensions of Entrepreneurial Organizational Culture and Creativity in Faculty Members of Tehran University - Riazi, Zohreh (Iranian Journal of Educational Sociology, 2022)
Purpose: Entrepreneurship culture needs to have a favorable environment for innovation and creative responsiveness to environmental needs. Entrepreneurial culture emphasizes identifying, supporting, and developing creative talents. The prevalence of this kind of culture makes universities, in their confrontation with the threats of competitors, the innovation, creativity, and risk-taking to exploit the opportunities necessary. Creativity is a complex and multidimensional phenomenon that affects a variety of factors. These factors may be a specific environmental or cultural force in an organization seeking to create value and prosperity. Methodology: The purpose of this research is to investigate the relationship The dimensions of entrepreneurial organizational culture and creativity are in the faculty of Tehran University. The research method used is a descriptive method from the survey branch. For this purpose, a sample of 262 faculty members from the colleges of Tehran University was selected and studied using the Cochran formula. To collect information, McGuire's Entrepreneurial Organizational Culture Dimensions Questionnaire (2003) and Islan Powell's Creativity and Innovation Scale (2006) were used. Pearson correlation test and linear regression models were used to investigate the existence of this relationship. Findings: The results of the research show that in women, only the effect of recreation and entertainment has been significant on the creativity of professors. And in men, the effect of recreation, hobbies, and communication on the creativity of professors has been meaningful. Discussion: The impact of other areas of organizational culture on the creativity of professors in male and female teachers was not meaningful.